2013
DOI: 10.1155/2013/247018
|View full text |Cite
|
Sign up to set email alerts
|

Growth ofMycobacterium aviumsubsp.paratuberculosis,Escherichia coli, andSalmonellaEnteritidis during Preparation and Storage of Yogurt

Abstract: The purpose of this study was to determine the viability of Mycobacterium avium subsp. paratuberculosis (MAP), Escherichia coli (E. coli), and Salmonella Enteritidis (S. Enteritidis) during preparation and refrigerated storage of yogurt. Three yogurts were prepared using pasteurized commercial milk. Each yogurt was artificially contaminated with (1) MAP, (2) E. coli + S. Enteritidis, and (3) MAP + E. coli + S. Enteritidis. Samples were taken during and after the fermentation process until day 20 after inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In the same context, Osaili et al (18) reported a large increase of E. coli O157:H7 count of 3.05 log CFU mL -1 during the fermentation process. After the fermentation process, we found similar results as Ogwaro et al (20) and Cirone et al (21) , who reported an increase of E. coli O157:H7 counts from 5 CFU mL -1 to 8-9 log CFU mL -1 and 5.3 CFU mL -1 to 6.4 log CFU mL -1 after 24 h of fermentation, respectively.…”
Section: Resultssupporting
confidence: 89%
“…In the same context, Osaili et al (18) reported a large increase of E. coli O157:H7 count of 3.05 log CFU mL -1 during the fermentation process. After the fermentation process, we found similar results as Ogwaro et al (20) and Cirone et al (21) , who reported an increase of E. coli O157:H7 counts from 5 CFU mL -1 to 8-9 log CFU mL -1 and 5.3 CFU mL -1 to 6.4 log CFU mL -1 after 24 h of fermentation, respectively.…”
Section: Resultssupporting
confidence: 89%
“…An inactivation of pathogenic bacteria in fermented dairy products, including yogurt, has been observed in many studies (Rubin and Vaughan 1979, Rubin et al 1982, Alm 1983, Kotz et al 1990, Issa and Ryser 2000, Hlvarez-Ordóñ ez et al 2013, Cirone et al 2013. The main mechanism of bactericidal effect of yogurt on foodborne pathogens seems to be the decline in pH due to lactose fermentation by Lactobacillus delbrueckii ssp.…”
Section: Discussionmentioning
confidence: 96%
“…pH, competitive microflora), storage conditions (temperature) and other environmental circumstances. Cirone et al (2013) proved that pathogenic bacteria like Mycobacterium avium subsp. paratuberculosis, E. coli, and S. Enteritidis could survive the fermentation process during yogurt production and were not inactivated by low pH levels followed by cold storage for at least 20 days.…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of pathogenic bacteria in fermented milk products, including yogurt, was found by many authors (Rubin and Vaughan 1979, Rubin et al 1982, Alm 1983, Kotz et al 1990, Issa and Ryser 2000, Á lvarez-Ordóñ ez et al 2013, Cirone et al 2013. The main mechanism of bactericidal effect of yogurt on Salmonella and other pathogens seems to be the decline in pH due to lactose fermentation and the production of organic acids, mainly lactic acid, by Lactobacillus delbrueckii ssp.…”
Section: Discussionmentioning
confidence: 97%
“…However, these bacteria may survive in final product for some time dependent on the type of product, its pH, storage temperature and other environmental conditions. Cirone et al (2013) presented evidence that pathogenic bacteria like Mycobacterium avium subsp. paratuberculosis, E. coli, and S. Enteritidis could survive yogurt fermentation conditions and low pH levels followed by refrigerated storage for at least 20 days.…”
Section: Introductionmentioning
confidence: 99%